On the non-stationary distribution of the length of the queue of the single server system - Ivnickij, A. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. А. Ивницкий. О нестационарном распределении длины очереди однолинейной системы массового обслуживания A. Ivnickis. Apie vienos linijos masinio aptarnavimo eilės ilgio nestacionarų pasiskirstymą